Desaﬁos da modelagem de aplicações multimídia com múltiplos efeitos sensoriais - Mattos, Douglas P.; Barreto, Fábio; Amorim, Glauco F.; Santos, Joel A. F. dos; Muchaluat-Saade, Débora C. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2016: Anais Estendidos do XXII Simpósio Brasileiro de Sistemas Multimídia e Web, 2016)
Multimedia applications are usually composed by audiovisual content. Multiple sensorial media, or mulsemedia, applications consider the use of sensorial eﬀects that can stimulate touch, smell and taste, in addition to hearing and sight. Traditional multimedia conceptual models, and consequently multimedia authoring declarative languages, which are used for representing multimedia applications, do not support the deﬁnition of multiple sensorial eﬀects. This paper discusses new issues and requirements brought by mulsemedia applications that should be considered in the deﬁnition of a mulsemedia conceptual model. A new model must be deﬁned in order to extend multimedia authoring languages to be capable of representing mulsemedia content.